Energy saving in six doors walk-in cooler - Somchai Pattana; Chutchawan Tantakitti; Kengkamon Wiratkasem (Energy Reports, 2020)
Two Identical six doors walk-in coolers are installed with the fixed speed compressor and the digital scroll compressor. Both compressors have almost the same cooling capacity of 8 kW at the evaporating temperature of -6.7~°C and the ambient temperature of 32~°C. The heating loads from the envelope, the water bottles, and the air change during the door closing and opening of both coolers are the same. The temperature of the room in front of the cooler doors is controlled at 25~°C. They are set to have a similar average room temperature and a similar cool down. Both units are run 24~h per day for 30 days during which the ambient temperature and the power consumption are recorded. The results show that for Thailand weather, yearly saving is 20% for the digital scroll as compared with the fixed speed compressor.
Keywords: 330; Digital scroll compressor; Energy saving; Fixed-speed compressor; Walk-in cooler